Enhancement of local electric field in core-shell orientation of ellipsoidal metal/dielectric nanoparticles - Ismail, A.A.; Gholap, A.V.; Abbo, Y.A. (Condensed Matter Physics, 2017)
In this paper it is shown that the enhancement factor of the local electric field in metal covered ellipsoidal
nanoparticles embedded in a dielectric host matrix has two maxima at two different frequencies. The second
maximum for the metal covered inclusions with large dielectric core (small metal fraction p) is comparatively
large. This maximum strongly depends on the depolarization factor of the core L⁽¹⁾z
, keeping that of the shell
L⁽²⁾z
constant and is less than L⁽¹⁾z
. If the frequency of the external radiation approaches the frequency of
surface plasmons of a metal, the local field in the particle considerably increases. The importance of maximum
value of enhancement factor |A|²
of the ellipsoidal inclusion is emphasized in the case where the dielectric core
exceeds metal fraction of the inclusion. The results of numerical computations for typical small silver particles
are presented graphically. В цiй статтi показано, що коефiцiєнт пiдсилення локального електричного поля в елiпсоїдних частинках
з металевим покриттям, вставлених в дiелектричну матрицю, має два максимуми при рiзних частотах.
Другий максимум для включень з металiчним покриттям з великим дiелектричним кором (мала фракцiя
металу p) є порiвняно великим. Цей максимум сильно залежить вiд коефiцiєнту деполяризацiї кору L⁽¹⁾z

,
коли L⁽²⁾z для оболонки залишається постiйним i меншим нiж L⁽¹⁾z

. Якщо частота зовнiшнього випромiнювання наближається до частоти поверхневих плазмонiв металу, локальне поле в частинцi значно зростає. Наголошується, що максимальне значення коефiцiєнта пiдсилення |A|²
елiпсоїдального включення
стає особливо важливим у випадку, коли дiелектричний кор перевищує металеву фракцiю включення.
Графiчно представленi результати числових обчислень для типових малих срiбних частинок.